"Diversity, " immigration, and the new American multi‐racial hierarchy. Issue 3 (2014) - Myrtle P. Bell; Dennis Marquardt; Daphne P. Berry
<x xml:space="preserve"> Abstract </x> Purpose – This paper aims to analyze the new multi‐racial hierarchy in the USA. The authors propose that despite increasing diversity, a multi‐racial hierarchy of privilege and disadvantage continues to exist. Due to the history of anti‐Black discrimination and stereotyping in the USA, employers prefer native and immigrant non‐Blacks to native and immigrant Blacks, and use non‐Blacks to claim organizational diversity success. Design/methodology/approach – The authors propose that a multi‐racial hierarchy, ordered as Whites, Non‐White Non‐Blacks, and Collective Blacks now exists, and use history, relevant theory, existing research, and government data to support their ideas. Findings – Evidence suggests that despite increased diversity, Whites remain most privileged, Blacks least privileged, and Asians and Hispanics tend to comprise the middle of the hierarchy. Even in organizations that are "diverse, " a multi‐racial hierarchy results in different compensation, promotion, and layoff rates and differential treatment across groups. Research limitations/implications – Diversity within and across different racial and ethnic groups should be investigated. Employers' apparent diversity success may obscure the continued dominance of Whites, disadvantage of Blacks, and a color‐based multi‐racial hierarchy. Practical implications – Analyses of human resources data could help organizations identify and avoid discrimination and inequality even in "diverse" organizations. Originality/value – This paper focuses on the meaning of a new multi‐racial hierarchy in ways that have not been previously considered.